Latitude does not influence cavity entrance orientation of South American avian excavators. Issue 1 (7th January 2021) - Ojeda, Valeria; Schaaf, Alejandro; Altamirano, Tomás A; Bonaparte, Bianca; Bragagnolo, Laura; Chazarreta, Laura; Cockle, Kristina; Dias, Raphael; Di Sallo, Facundo; Ibarra, J Tomás; Ippi, Silvina; Jauregui, Adrián; et al.
Abstract: In the Northern Hemisphere, several avian cavity excavators (e.g., woodpeckers) orient their cavities increasingly toward the equator as latitude increases (i.e. farther north), and it is proposed that they do so to take advantage of incident solar radiation at their nests. If latitude is a key driver of cavity orientations globally, this pattern should extend to the Southern Hemisphere. Here, we test the prediction that cavities are oriented increasingly northward at higher (i.e. colder) latitudes in the Southern Hemisphere and describe the preferred entrance direction(s) of 1, 501 cavities excavated by 25 avian species ( n = 22 Picidae, 2 Trogonidae, 1 Furnariidae) across 12 terrestrial ecoregions (15°S to 55°S) in South America. We used Bayesian projected normal mixed-effects models for circular data to examine the influence of latitude, and potential confounding factors, on cavity orientation. Also, a probability model-selection procedure was used to simultaneously examine multiple orientation hypotheses in each ecoregion to explore underlying cavity-orientation patterns. Contrary to predictions, and patterns from the Northern Hemisphere, birds did not orient their cavities more toward the equator with increasing latitude, suggesting that latitude may not be an important underlying selective force shaping excavation behavior in South America. Moreover, unimodal cavity-entrance orientations were not frequent among the ecoregions analyzed (only in 4 ecoregions), whereas bimodal (in 5 ecoregions) or uniform (in 3 ecoregions) orientations were also present, although many of these patterns were not very clear. Our results highlight the need to include data from under-studied biotas and regions to improve inferences at macroecological scales. Furthermore, we suggest a re-analysis of Northern Hemisphere cavity orientation patterns using a multi-model approach, and a more comprehensive assessment of the role of environmental factors as drivers of cavity orientation at different spatial scales in both hemispheres. Lay Summary: We tested the hypothesis that avian excavators (e.g., woodpeckers) increasingly orient their cavities toward the equator (sun) as latitude increases (i.e. colder climate), between 15°S and 55°S in the Southern Hemisphere. We found no evidence that latitude influenced orientation. The preferred entrance direction(s) of 1, 501 cavities excavated by 25 South American avian excavators from 12 ecoregions (bioclimatic areas) were bimodal (5 ecoregions), followed by unimodal (4 ecoregions), and uniform (3 ecoregions). The patterns of cavity orientation at the ecoregions considered, and the lack of relationship with latitude differed strikingly from previous studies from the Northern Hemisphere, which highlights the importance of using multi-model analytical approaches for circular data, as well as the need to include understudied biotas to improve inferences in macroecology.